Correlation between infection of herpes virus family and liver function parameters: a population-based cross-sectional study - Cui, Yali; Huang, Xiaocui; Wang, Xia; Li, Yingying; Tang, Chao; Wang, Hong; Jiang, Yongmei (The Journal of Infection in Developing Countries, 2017)
Introduction: To evaluate the relationship between seropositivity to herpes virus family and liver function parameters in children from southwest China. Methodology: A 2-year cross-sectional retrospective study of 6,396 children aged 6 months to 12 years was performed. All participants underwent physical examination and liver function tests. Results: Of the children, 622 were positive for EBV, HSV, or CMV IgM, with dramatic changes in liver function parameters. Aspartate aminotransferase and alanine aminotransferase levels were negatively correlated with EBV-IgM and hepatocellular injuries in children < 3 years of age, whereas a positive correlation between lactate dehydrogenase (LDH) and EBV-IgM and hepatocellular injuries was documented in children < 1 year of age. In those < 1 year and 3–6 years of age, HSV-IgM seropositivity was positively correlated with indirect bilirubin and γ-glutamyl transferase. The percentage of children < 1 year of age with positive CMV-IgM was 72.8% (158/217), approximately five times higher than that in those 1–3 years. Sixty-three children were infected with two pathogens simultaneously. Abnormal levels of LDH were observed in 85.71% of children simultaneously infected with CMV and HSV, 77.78% for CMV and EBV, 83.33% for EBV and HSV, and irregular levels of AST were noted in 69.19% of children infected with CMV and HSV, 77.78% for CMV and EBV, and 83.33% for EBV and HSV. Conclusions: Seropositivity to herpes virus family was correlated with abnormal liver function parameters across years of age. Clinicians should aim to protect the liver function of children infected with herpes viruses.